A cost effective cultivation medium for biocalcification of Bacillus pasteurii KCTC 3558 and its effect on cement cubes properties - S. Yoosathaporn (2018)
© 2016. Application of carbonate precipitation induced by Bacillus pasteurii for improving some properties of cement has been reported. However, it is not yet successful in commercial scale due to the high cost of cultivation medium. This is the first report on the application of effluent from chicken manure bio-gas plant, a high protein content agricultural waste, as an alternative growth medium for carbonate precipitation by B. pasteurii KCTC3558. Urease activity of B. pasteurii KCTC3558 cultured in chicken manure effluent medium and other three standard media were examined using phenate method. The highest urease production was achieved in chicken manure effluent medium (16.756 U mg-1protein). Cost per liter of chicken manure effluent medium is up to 88.2% lower than other standard media. The most effective cultivation media was selected for carbonate precipitation study in cement cubes. Water absorption, voids, apparent density and compressive strength of cement cubes were measured according to the ASTM standard. The correlation between the increasing density and compressive strength of bacterial added cement cube was evident. The density of bacterial cement cube is 5.1% higher than control while the compressive strength of cement mixed with bacterial cells in chicken manure effluent medium increases up to 30.2% compared with control. SEM and XRD analysis also found the crystalline phase of calcium carbonate within bacterial cement which confirmed that the increasing density and compressive strength were resulted from bacterial carbonate precipitation. This study indicated that the effluent from chicken manure bio-gas plant could be used as an alternative cost effective culture medium for cultivation and biocalcification of B. pasteurii KCTC3558 in cement.